Urgency of Akad as Sharia Economic Consumer Protection Against Rahn Transaction - Ika; Yunus, Nur Rohim (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
This study aims to determine the urgency of the pawn transaction akad (agreement) between consumers and sharia pawning institutions. The conceptual approach is the approach used in normative research, as well as the analytical approach needed in normative research. Primary sources are taken from books, journals, proceedings, statutory regulations, and Islamic economic law. The results of this research show that the protection of customers of rahn transactions (pawning) is a very important part of applying the principle of pleasure and the principle of justice between debtors and creditors as outlined in a written form called a contract (akad) or agreement. Customer protection can occur, if the harmonious and legal conditions of the contract (contract) are fulfilled by implementing the principle of equality and equality (al-musawah), in which the parties who contract an agreement have a very close relationship to fulfill their rights and obligations, of course. done by both of them for the performance in the contract to be effective.